Pincer‐Type Mesoionic Carbene Nickel(II) Complexes: Synthesis, Properties, Reactions, and Catalytic Application to the Suzuki–Miyaura Coupling Reaction of Aryl Bromides. Issue 10 (18th February 2022) - Matsubara, Kouki; Tomomatsu, Kanta; Tajiri, Ayame; Watanabe, Arisa; Koga, Yuji; Ishikawa, Ryuta; Yamada, Yuji
Abstract: Tridentate pincer‐type triazolylidene nickel(II) complexes have been prepared and characterized. Despite increasing interest in the new series of mesoionic carbene (MIC) ligands in the field of homogeneous catalysis, pincer‐type MIC metal complexes have rarely been used as catalysts, and there are few studies on MIC nickel complexes. Herein, MIC nickel(II) halide complexes were synthesized from their silver analogues and fully characterized. An anion exchange reaction with silver tetrafluoroborate in acetonitrile gave a dicationic acetonitrile complex in good yield. A comparison of the structures and frontier orbitals between the MIC‐ and NHC‐nickel(II) chloride complexes has revealed that these complexes are comparable in nature. However, their use in the Suzuki–Miyaura (SM) cross‐coupling reaction of aryl bromides with phenylboronic acid requires different conditions to provide sufficient results. Abstract : Tridentate, pincer‐type triazolylidene nickel(II) complexes have been prepared and fully characterized. The complexes have electronic and structural properties similar to their corresponding NHC complex. However, the catalytic Suzuki–Miyaura coupling reaction of aryl bromides required different conditions but showed comparable activity in catalysis.